The Survey of Educational Facilities and Present The Kinds of Program Staff development of Nursing Office in Hospital of Medical Science in Tehran , IRAN in 1997 - H Emamzadeh Ghasemi (Tehran University of Medical Sciences, 2000)
This is a quasi-Experimental research, which carried out inorder to determine the effect of applying executive in - service education model on quality of nursing care. For this purpose /email's general surgery unit in Bagiatalah hospital was selected (randomaizly) in order to case unit, and then in Najmieh hospital a unit control wasselected with same characteristic 0/the case unit. 30 sample 0f patients were selected/or quality control in each unit(inafterandbeforeintervention).Datagatheredwithducomentation checklist, patient assesment checklist, educational needs questionnaire and nursing practice evaluation checklist.The planning of educational performed based on quality of nursing care and educational needs assesment of nurses in case unit. Then researcherwithheadnurse applied planned educational model for one month and then the headnurse continued it for two more months in case unit. In this model headnurs lead nurses during executive educational model. After applied this educational model and quality control of nursing care in each unit, finding showed that significant quality care increased in case unit (20%), also it showed significant increased 250%. In quality of patient education (The scale of quality nursing care) incare unit rather than other. In this way hypotesis of research is confirmed (P=0/002) that executive in - service education model can increase quality of nursing care.